Are there differences on spray deposit distribution pro-duced on citrus canopies by conventional and low-drift nozzles? - Garcerá, Cruz; Salcedo, Ramón; Moltó, Enrique; Chueca, Patricia (EurAgEng, 2022)
Air injection nozzles are often recommended to reduce drift, which is one of the major pollu-tion sources caused by the application of plant protection products on fruit trees. However, it is important to know if the use of low-drift nozzles may affect the efficacy of treatments. This work is aimed at providing scientific evidence to asses if there are changes in the deposition pattern on citrus canopies when using conventional (cone) and low-drift (air injection) nozzles and discuss the consequences on efficacy of pesticides. Results showed that the air injection nozzles did not affect deposition in the conditions of the experiments, so they suggest that these nozzles can be regarded as a good alternative to the conventional ones.